Left Atrial Ball-Shaped Thrombus with Concomitant Biatrial Appendage Thrombi in a Patient with Prior Mitral Valve Replacement - Kanako Akamatsu; Takahide Ito; Kazushi Sakane; Yumiko Kanzaki; Koichi Sohmiya; Masaaki Hoshiga (Case Reports in Cardiology)
We reported a 67-year-old woman in whom large atrial thrombi were found by chance during discontinuation of therapeutic anticoagulation. The patient, with a history of mitral valve replacement surgery, had stopped anticoagulation for months because of intractable gastrointestinal bleeding, during which she was found to have 3 large thrombi in the atria on transesophageal echocardiography: left atrial free-floating ball-shaped thrombus, left atrial appendage thrombus, and right atrial appendage thrombus. One month following diagnosis, she still had the free-floating thrombus despite adequate anticoagulation. Free-floating ball-shaped thrombus is a rare finding observed on echocardiography in patients with mitral valve disease and an even rarer finding in case of appendage thrombi coexisting.